Migrants in Countries in Crisis: The Experiences of Ghanaian and Nigerien Migrants during the Libyan Crisis of 2011 (African Human Mobility Review, 2021)
Using the experiences of Ghanaian and Nigerian migrants who were implicatedin the 2011 Libyan crisis as a case study, this paper highlights the importance ofexamining micro-level factors in explaining migration decision-makingprocesses. It therefore challenges the uncritical use of macro-level factors asexogenous ‘root causes’ of migration especially in developing country contexts.Adopting mainly qualitative approaches among seventy-five key informantsfrom six distinct categories, the study finds that migration culture, householdlivelihood aspirations, geographical propinquity, the existence of social networksand migrant smuggling rings motivate migrations to Libya. The paper alsochallenges scholarship on the 2011 Libyan crisis that treats the experiences ofsub-Saharan African (SSA) migrants in the country as an undifferentiated group.The paper concludes that within a developing country context, the politicaleconomy of the origin country contributes to the establishment, over time, of amigration culture especially among youth who feel trapped in ‘waithood’ and areunable to realize basic socio-cultural and economic markers in life. The paperrecommends the regionalization of evacuation and repatriation programmes tofacilitate the timely extraction of trapped migrants from countries in crisis.